Performance evaluation and measurement of SMEs king of honey using the green SCOR method - Fitriana, Risa Naili; Ifada, Alda Bernika; Lestari, Tiffany Ovilia Putri Dwi; Hidayah, Sayidah Rohmatul (Journal of Soft Computing Exploration, 2022)
Assessment of the application of the concept of Green Supply Chain Management (GSCM) in each business unit is something that is important to do considering that currently environmental issues are a very urgent matter. Therefore, this study will focus on assessing the GSCM process and measuring performance to determine the value of GSCM performance in King of Honey SMEs. The method used in this research is Green SCOR with 6 management processes, namely plan, source, make, delivery, return, and waste. From the research conducted, the priority level of GSCM indicators and the value of GSCM performance on King of Honey SMEs are generated. The results of this study showed that the total performance value of GSCM King of Honey in September was 86.03, October was 86.45 and November was 86.48.